DEVELOPMENT OF HYBRID COMPRESSION ON LANDSAT-8 IMAGERY FOR QUICK-LOOK AND STORAGE SAVINGS - Yuvita Dian Safitri; Wismu Sunarmodo; Ayom Widipaminto (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2020)
Compression is an important part of management for remote sensing images. Various methods were developed to produce the best compression results. This paper proposes a hybrid method that combines the methods of PCA, DCT, DWT, and LZW to produce the smallest file size with the best PSNR value on Landsat-8 images. The stages carried out in this study include; determine random cloud-free datasets at maximum zoom, specify n_component using PCA, the compression process in bands 6, 5, and 2; comparison of compression techniques (time consumption - PSNR - file size), as well as visual inspection of compression results. The experimental results show that the file size of Landsat-8 image dataset using the hybrid method ranges from 22-55 kB with a processing time of less than 2 seconds using the python programming language. However, the PSNR value produced is still below the other methods with a range of 48-51%.